Israel and the Individual in Matthew and Midrash: Reassessing “True Israel” - Schaser, Nicholas J. (Religions, 2021)
Since the Holocaust, New Testament scholarship has become increasingly sensitive to issues of Christian anti-Judaism. While many Matthean specialists have acknowledged the problems with polemical interpretations of the Gospel, the idea that Matthew presents Jesus and/or the church is the “true Israel” continues to enjoy broad acceptance. The scholarly conflation of Jesus and Israel recycles the Christian polemic against a comparatively inauthentic or inadequate Judaism. This article argues that Matthew does not present Jesus or his church as the true Israel, and that the Jesus-as-Israel interpretation could be refined by comparing the Gospel with later rabbinic discussion that connects Israel with biblical individuals. Genesis Rabbah 40:6 juxtaposes verses about Abraham and Israel to reveal a comprehensive scriptural relationship between the nation and the patriarch without devaluing either party. The rabbis’ theological thesis is predicated on both similarity and separation between Abraham and his offspring. Insofar as both Matthew and Midrash present similar biblical content and exegesis, a comparative analysis can provide Gospel commentators with a view of the Jesus-Israel paradigm that avoids the Christianization of “true Israel.”